2020
DOI: 10.1039/d0tc03334k
|View full text |Cite
|
Sign up to set email alerts
|

Soft ionic liquid based resistive memory characteristics in a two terminal discrete polydimethylsiloxane cylindrical microchannel

Abstract: This paper proposes a novel soft ionic liquid (IL) electrically functional device that displays resistive memory characteristics using poly (acrylic acid) partial sodium salt (PAA-Na+:H2O) solution gel and sodium hydroxide...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…During each voltage sweep, this process is repeated, and the high metallization process occurs on both electrodes. Due to the metallization on both electrodes, the conductance decreases on the side, and the device shows multistate resistive switching with depression on both sides [ 23 ] on the electrode during repeated voltage sweep, as shown in Figure 2a,b. By applying the positive and negative voltage sweep, the current starts to decrease in both voltage regions.…”
Section: Resultsmentioning
confidence: 99%
“…During each voltage sweep, this process is repeated, and the high metallization process occurs on both electrodes. Due to the metallization on both electrodes, the conductance decreases on the side, and the device shows multistate resistive switching with depression on both sides [ 23 ] on the electrode during repeated voltage sweep, as shown in Figure 2a,b. By applying the positive and negative voltage sweep, the current starts to decrease in both voltage regions.…”
Section: Resultsmentioning
confidence: 99%
“…[46] Bae et al developed an ionic-liquid-based soft memory device for fluid-based logic operations using a Cu/ (PAANa þ :H 2 O):(NaOH)/Cu structure in a cylindrical microchannel. [47] Zhou et al found that Ag/TiO x nanobelt/Ti memory device could evolve from a non-standard faradic capacitance in dry circumstance to a battery-like capacitance at a moisture atmosphere (35-45%), and finally to the RS state at the RH of 95-100%. [48] OHPs materials, in particular, being much sensitive to oxygen, H 2 O and light, can definitely serve as promising proxies for multifunctional RRAM applications.…”
Section: Multifunctional Rrammentioning
confidence: 99%
“…In 2008, a memristor was for the first time released by St. Williams in the HP lab . After this, new materials were introduced for memristor fabrication and optimization, including biomaterials, soft materials, 2D materials, and metal oxides. Different device structures are proposed to fabricate memristors on a larger scale in a crossbar array, including an active layer based on a single material , and a composite or heterojunction of two materials . However, the crossbar array faces a sneak current problem .…”
Section: Introductionmentioning
confidence: 99%